Mutational analysis of cell cycle arrest, nuclear localization and virion packaging of human immunodeficiency virus type 1 Vpr. - Di Marzio, P (1995)
Human immunodeficiency virus type 1 Vpr is a virion-associated, regulatory protein that is required for efficient viral replication in monocytes/macrophages. The protein is believed to act in conjunction with the Gag matrix protein to allow import of the viral preintegration complex in nondividing cells. In cells, Vpr localizes to the nucleus. Recently, we showed that Vpr prevents the activation of p34cdc2-cyclin B. This results in arrest of Vpr-expressing cells in the G2/M phase of the cell cycle. Here, we use a panel of expression vectors encoding Vpr molecules mutated in the amino-terminal alpha-helical region, the central hydrophobic region, or the carboxy-terminal basic region to define the functional domains of the protein. The results showed cell cycle arrest was largely controlled by the carboxy-terminal basic domain of the protein. In contrast, the amino-terminal alpha-helical region of Vpr was required for nuclear localization and packaging into virions. The carboxy terminus appeared to be unnecessary for nuclear localization. In the alpha-helical region, mutation of Ala-30 to Pro resulted in a protein that localized to the cytoplasm. Surprisingly, fusion of Vpr to luciferase resulted in a molecule that failed to localize to the nucleus. In addition, we show that simian immunodeficiency virus Vpr, but not Vpx, induces G2 arrest. We speculate that Vpr has two sites for interaction with cellular factors: one in the alpha-helical region that specifies nuclear localization and one in the carboxy-terminal domain that is required for Cdc2 inhibition.